2007
DOI: 10.1108/00012530710725214
|View full text |Cite
|
Sign up to set email alerts
|

Information literacy amongst UK SMEs: an information policy gap

Abstract: Purpose – The purpose of this paper is to explore information literacy amongst small- and medium-sized businesses (SMEs) in the UK and the USA and argue that information policy in the UK has not given sufficient attention to helping these companies navigate the ever-increasing volumes of information accessible over the internet. Design/methodology/approach – A combination of primary and secondary data have been used. The primary data consists of a survey of UK SMEs, which explored how these companies use the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 6 publications
0
29
0
Order By: Relevance
“…For example, in one study, employees reported that they do not know what resources are available to them and therefore waste valuable time looking at information from inappropriate sources, which may also compromise the quality of their work (Cheuk, ). Similarly, De Saulles () attributed loss of business income in the United Kingdom to inefficient searching for information. Others have reported that many workforce employees lack the skills to use information effectively (Head, ; Raish & Rimland, ; Thompson, ).…”
mentioning
confidence: 99%
“…For example, in one study, employees reported that they do not know what resources are available to them and therefore waste valuable time looking at information from inappropriate sources, which may also compromise the quality of their work (Cheuk, ). Similarly, De Saulles () attributed loss of business income in the United Kingdom to inefficient searching for information. Others have reported that many workforce employees lack the skills to use information effectively (Head, ; Raish & Rimland, ; Thompson, ).…”
mentioning
confidence: 99%
“…With such a variety of information readily available by way of the Internet and search engines, many believe that they are capable of finding what they need using simple Internet searches. A comfort with using computers and other technologies, including mobile devices, often leads individuals to overestimate their searching abilities, thereby underestimating their need for information literacy training (Bruce 1999;Campbell, 2004;DeSaulles, 2007;Jensen, et al, 2010;Ramesha, 2008;Spiranec & Pejova, 2010;Underwood, 2009). The work of the Information Literacy Initiative addresses several of these issues.…”
Section: Resultsmentioning
confidence: 97%
“…There is often confusion between computer literacy and information literacy (Bruce, 1999;Campbell, 2004;DeSaulles, 2007;Jensen, King, Davis, & Guntzviller, 2010;Ramesha, 2008;Spiranec & Pejova, 2010;Underwood, 2009). Some of the problems that arise from being able to successfully navigate the technology, but not the information, include the use of out-of-date information, being unaware of important resources, and the assumption that Google is the best approach to finding information (Cheuk, 2008).…”
Section: The Workplacementioning
confidence: 96%
See 2 more Smart Citations